Resistensi Masyarakat Aceh terhadap Pengungsi Muslim Rohingya di Era Digital - Saka, Putri Ananda; Saka, Zidan Abdul Jabar; Cahyani, Novita (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The arrival of Rohingya Muslim refugees in coastal Aceh led to a rejection response from the local community. Resistance is not necessarily present but the result of accumulated experiences and negative contacts built between local communities and previous refugees. In line with that, this article aims to map the resistance that is present in the frame of digital media. More specifically, this article wants to explain about: 1) the forms of resistance present in the framing of online news media, 2) the forms of resistance found in social media, and 3) the controversy between the community and pro Rohingya organizations. In order to obtain the desired data, this article uses internet studies and a descriptive qualitative approach. The results show that resistance in online news framing is divided into three forms, namely news that broadcasts community resistance in the form of demonstrations, expulsion of Rohingya boats, to anarchist actions and evictions at refugee camps. In the realm of social media, recorded resistance develops into a universal issue that is produced and reproduced. The resistance manifested in feed posts, video reels content, and discourse in comments gradually shifted into expressions of hatred towards Rohingya refugees. The rejection continues to pressure international and national institutions for the expulsion of Rohingya refugees. Thus, it is necessary to socialize digital literacy and strengthen the values of diversity in the community in order to build awareness in the wise use of social media.